THEORETICAL BEAM HARDENING CORRECTION FOR INDUSTRIAL X-RAY COMPUTED TOMOGRAPHY - Ahmed, Osama Mhmood Hamed; Song, YuShou; Zhaoyang, Xie (Journal of Engineering and Technological Sciences, 2019)
Beam hardening is a significant artifact that comes from the polychromatic nature of the X-ray source in computed tomography. It appears because the object tends to absorb more low-energy photons within the beam, which leads to a nonlinear relationship between attenuation and material thickness. As a result, the reconstructed image is spoiled. This work articulates an approach to promoting the correction of MeV X-ray beam hardening. In order to calculate the attenuation of the polychromatic beam, the following terms were evaluated: the energy spectra S(E) for sets of X-ray spectra with a maximum energy of 2, 4, 6 and 9 MeV were simulated using the Geant4 toolkit; the counting efficiency ?(E) was estimated based on the Lifton method; and the attenuation coefficient µ(E) was taken from the NIST database. The non-linear relationship between the attenuation and the thickness of iron was investigated. The beam hardening for each energy set was successfully corrected by polynomial fitting, transforming the polychromatic attenuation data into equivalent monochromatic data. The corrected attenuation was used to estimate the penetration capability of the X-ray source and produced a result that was consistent with what has been reported in the literature.